Semiderivations with Power Values on Lie Ideals in Prime Rings - Shuliang Huang (Український математичний журнал, 2013)
Let R be a prime ring, let L a noncentral Lie ideal, and let f be a nonzero semiderivation associated with an automorphism σ such that f(u)ⁿ  = 0 for all u ∈ L; where n is a fixed positive integer. If either Char R > n + 1 or Char R = 0; then R satisfies s₄; the standard identity in four variables. Нехай R — просте кільцє, L — нецентральний ідеал Лі та f — ненульова напівпохідна, асоційована з автоморфiзмом a таким, що f(u)ⁿ=0 для всіх uЄL, де n — фіксоване натуральне число. Якщо Char R>n+1 або Char R=0, то R задовольняє стандартну тотожність s₄ у чотирьох змінних.